Diseño de un biodigestor que genere biogás para el aprovechamiento del excremento avícola. (2020)
The present project consists in the design of a biodigester for the generation of biogas using as fuel the excrement of laying hens raised in the farm " my farm eggs the golden " of the sidewalk the Triunfo, corregimiento the Caguán of the city of Neiva-Huila, as a first step were determined the physico-chemical variables of the mixture between chicken manure and water, for this the chicken was collected produced by 1325 laying hens for six months and from a pig kept on the farm, which would function as a substrate that accelerates anaerobic digestion, as a result an average of 33.46 kg/day was obtained, after collection pH tests were performed at different ratios between hens, and water to define the percentage of mixture with which the biodigester would be supplied, being that of 40% substrate (Chiken manure- swine manure ) and 60% water, the most suitable for the functioning of the biodigester. A simulation of the development of the biodigester was carried out using a demo version of the software Simba #biogas, demonstrating that approximately 10 m^3 of biogas produced monthly, based on volume of the organic load, was worked at a temperature of 35 °C, appropriate for the growth and development of bacteria, with this a retention time of 30 days was obtained, concluding that the production of biogas generated by poultry and pig excrement, can replace 50% of the gas used in the farm, replacing consumption for 15 days a month saving $30,850